2010
DOI: 10.20473/ijtid.v1i3.2183
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection in Hemodialysis Patients: Comparison of the Surabaya Dialysis Center and Juntendo University Hospital Dialysis Centre

Abstract: Hepatitis C virus infection is highly prevalence in chronic hemodialysis (HD) patients. The present study will compare prevalence of HCV positive population in difference countries where there are great contrasts in and diversity of care available to patients who have end stage renal disease. All serum samples of the 100 patients were tested for HCV antibodies, using third-generation enzyme immunoassay. The prevalence of anti-HCV was correlated with a history of blood transfusion and with duration of hemodialy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
1
2
Order By: Relevance
“…Unfortunately, blood transfusion, rather than erythropoietin treatment, is still being used to correct renal anemia in the hemodialysis unit. Consistent with previous studies [Saketi et al, ; Santoso et al, ], the duration of hemodialysis was independently and positively associated with the prevalence of HCV infection, supporting the hypothesis that nosocomial transmission was responsible for HCV infection within the hemodialysis unit.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Unfortunately, blood transfusion, rather than erythropoietin treatment, is still being used to correct renal anemia in the hemodialysis unit. Consistent with previous studies [Saketi et al, ; Santoso et al, ], the duration of hemodialysis was independently and positively associated with the prevalence of HCV infection, supporting the hypothesis that nosocomial transmission was responsible for HCV infection within the hemodialysis unit.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of HBV infection in this study was higher than that in another hemodialysis unit in Jakarta, but the prevalence of HCV infection was lower than that in hemodialysis units in Jakarta and Surabaya, where the prevalence rates were 97.9% and 88%, respectively [Budihusodo et al, ; Santoso et al, ]. However, these findings may simply represent the high prevalence of HBV and HCV in Java, independent of hemodialysis units.…”
Section: Discussioncontrasting
confidence: 51%
“…This figure is higher than the reported HCV seropositivity among the general population in Indonesia (1%) [ 13 ]. The seroconversion rate in our study was lower than the seroconversion rates reported from other hemodialysis units in Indonesia, that is, 38% in Jakarta and 88% in Surabaya [ 17 , 18 ]. Hepatitis C seroconversion in our dialysis unit was also lower than the seropositivity reported in studies in Brazil (46.7%), Libya (34.9%), and Egypt (34.8%) [ 8 , 19 , 20 ].…”
Section: Discussioncontrasting
confidence: 87%
“…Previous studies that investigated local HCV infection outbreaks within dialysis units found common evidence that suggests nosocomial infection with various risk factors related to the dialysis procedure, which were unique to each dialysis unit [2,15]. Accordingly, the duration of hemodialysis was reported as an independent risk factor for HCV transmission [2,[16][17][18]. Hemodialysis patients with hepatitis B and HIV infection also have a greater risk of HCV seroconversion [2].…”
Section: Introductionmentioning
confidence: 99%